Effects of heat treatment on metabolism of tobacco plants infected with Potato virus Y. (4th February 2021) - Hýsková, V.; Bělonožníková, K.; Doričová, V.; Kavan, D.; Gillarová, S.; Henke, S.; Synková, H.; Ryšlavá, H.; Čeřovská, N.
Abstract: Many factors affect successful virus propagation and plant defence responses. Heat shock protein (Hsp) expression after heat shock plays an ambiguous role in viral infection. On the one hand, Hsp70 participates in plant defence response; on the other hand, Hsp70 could interact with viral proteins and facilitate virus propagation. Here, we studied metabolic adaptations of Nicotiana tabacum L. subjected to heat shock (42 °C, 2 h) before or after inoculating the plants with Potato virus Y (potyvirus). RT‐qPCR and ELISA were used for potyvirus quantification. Hsp70 and Hsp90 isoforms were analysed by Western blotting. Salicylic, quinic and chlorogenic acid content was determined by LC‐MS. The activity of Hatch–Slack enzymes (as markers of potyviral infection in tobacco) and glycosidases was assayed. Application of heat shock before or after inoculation showed accelerated potyviral propagation in comparison with only inoculated plants. Plants exposed to heat shock and concurrently inoculated showed higher potyviral content, higher amount of Hsp70, together with late decline of quinic acid content and low chlorogenic acid content. Spread of potyviral infection correlated with enhanced salicylic acid content and activities of enzymes of the Hatch–Slack cycle, α‐ and β‐galactosidase, α‐mannosidase, α‐glucosidase and β‐N‐acetylhexosaminidase. Heat shock proteins accelerate potyviral propagation. The lower weight cytosolic and mitochondrial Hsp70 ( 50‐75 kDa) persist throughout the viral infection. Also, the plant defense response results in increase of salicylic and chlorogenic acids but decrease of quinic acid content. Abstract : Heat shock inducing expression of Hsps70 and 90 affected the content of phenolic acids (chlorogenic and quinic) and onset of potyviral infection in tobacco plants.